Isolation and Identification of Hydrocarbon-Degrading Bacteria that Tolerant to Saponin of Sapindus Rarak Plant - Evi Octaviany; Suharjono Suharjono; Irfan Mustafa (UIN Sunan Gunung Djati Bandung, 2019)
A commercial saponin as biosurfactant can reduce the surface tension of water and increase of hydrocarbon degradation. However, this saponin can be toxic to some hydrocarbonoclastic bac-teria. This study aimed to obtain bacterial isolates that were tolerant and incapable to degrade saponin, and to identify them based on 16S rDNA sequence. Bacteria were isolated from petroleum contaminated soil in Wonocolo Village, Bojonegoro Regency, East Java, Indonesia. The soil samples were acclimated using Bushnell-Haas (BH) broth with 0.5% crude oil at room temperature for 3 weeks. The culture was spread onto BH agar incubated at 30°C for 7 days. The first screened, isolates were grown in nutrient broth with addition of sap-onin 0%, 8%, and 12% (v/v) then incubated at 30°C for three days. The bacterial cell density was measured using a spectrophotometer. Second screened, the isolates were grown on BH broth with addition of 0.5% saponin as a sole carbon source, and their cell densities were measured. The selected isolates were identified based on 16S rDNA sequences. Among 34 bacterial isolates, nine isolates were tol-erant to 12% saponin. Three bacterial isolates IHT1.3, IHT1.5, and IHT3.24 tolerant to high concentration of saponin and did not use this substance as growth nutrition. The IHT1.3, IHT1.5, and IHT3.24 isolates were identified as Ochrobactrum pseudogrignonense (99% similarity), Pseudomonas mendocina (99%), and Ochrobactrum pi-tuitosum; (97%), respectively. Those three selected isolates are good candidates as hydrocarbon-degrading bacteria to bioremediation of soil contaminated crude oil. However, the combined activity of bacteria and saponin to degrade hydrocarbon needs further study.